The Port Chicago 50 [compact disc, unabridged] : disaster, mutiny, and the fight for civil rights - Sheinkin, Steve (Listening Library, 2014)
On July 17, 1944, a massive explosion rocked the segregated Navy base at Port Chicago, California, killing more than 300 sailors who were at the docks, critically injuring off-duty men in their bunks, and shattering windows up to a mile away. On August 9th, 244 men refused to go back to work until unsafe and unfair conditions at the docks were addressed. When the dust settled, fifty were charged with mutiny, facing decades in jail and even execution. This is a fascinating story of the prejudice that faced black men and women in America's armed forces during World War II, and a nuanced look at those who gave their lives in service of a country where they lacked the most basic rights.